ANALISIS FAKTOR PENDAPATAN DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN BARANG ELEKTRONIK PADA UD. DEWI SRI ELEKTRONIK LAMONGAN - Imam Tresno Edy; Kemal Farouq Mauladi; Yuhronur Efendi (STIE Mahardhika, 2020)
Research on consumer purchasing decisions is often done. In this study aims to partially and simultaneously determine the level of income and lifestyle variables on purchasing decisions. The population in this study all employees of UD.Dewi Sri Elektronik Lamongan numbered 50 people from the population taken 50 employees. Data collection techniques are done by giving questions to respondents using a questionnaire with a Likert scale because the answers of the instruments have different gradations. The analytical method used to analyze the effect of income and lifestyle variables on purchasing decisions is to use multiple regression analysis with the help of the SPSS version 20 statistical program. And test the hypothesis based on the p value> 0.05 then the alternative hypothesis is rejected and vice versa. From the research results, it is obtained that partially the level of lifestyle influences productivity on purchasing decisions, simultaneously the F test has a significant influence of independent variables with the dependent variable, so it can be concluded that lifestyle variables have a more dominant influence than income. Lifestyle is an activity such as the thing is people work, and a person's lifestyle will also affect the choice of an item that will be purchased, so that consumers will make a purchase decision on the goods needed by consumers UD.Dewi Sri Elektronik Lamongan